The 'Expansionary Fiscal Contraction Hypothesis' and Uncertainty About the Permanence of Fiscal Consolidations - Michael Bergman (Lund University, School of Economics and Management, Department of Economics, 2000)
This paper contrasts the effects of balanced-budget reductions in government consumption on private consumption in the permanent income model and a model allowing for precautionary savings. We compare impulse responses of private consumption to temporary and permanent shocks to government consumption when agents do not observe the shocks directly or can distinguish between temporary and permanent shocks. Our simulations suggest that uncertainty about the permanence of government consumption reductions affect both the impact and the duration of private consumption whereas precautionary saving motives only affect the impact.
Keywords: E21; E62; 330; Expansionary fiscal contraction; fiscal consolidations; uncertainty; precautionary savings